Apps That Motivate: a Taxonomy of App Features Based on Self-Determination Theory. Issue 140 (August 2020) - Villalobos-Zúñiga, Gabriela; Cherubini, Mauro
Highlights: Taxonomy of behavior-change applications. Designing effective behavior change interventions based on the Self-Determination Theory. Behavior change apps that support Self-Determination Theory Basic Psychological Needs for human motivation. Abstract: Nowadays, thousands of popular applications are designed to help users improve their lives through behavioural adjustment (e.g., meditate more, stay hydrated). However, our understanding of how certain design features align with constructs of behavior theories remain limited. We analyze 208 apps from the Apple App Store and identified 12 design features afforded by current tools that we classified according to the Self-Determination Theory. The taxonomy reported in this paper, we argue, provides a simple tool for designers to evaluate how specific features, and combination of features, may work to motivate users towards their desired goals. Additionally, the presented taxonomy is intended to help researchers test new interventions by discussing relevant research gaps.